Digital Storytelling: A Systematic Review of its Impact in Language Education - John, Emilia Andorshiye; Ukpai, Gift (PT FORMOSA CENDEKIA GLOBAL, 2025)
Digital Storytelling (DSt) has increasingly been recognized as an effective pedagogical tool in 21st-century education, leveraging multimedia elements to create engaging narratives that foster deeper learning and critical thinking. This study employed a systematic literature review following PRISMA guidelines, analyzing 50 peer-reviewed publications published between 2008 and 2024 that focused on the use of digital storytelling in language education. The results show that digital storytelling is highly effective in promoting lifelong learning, developing essential 21st-century skills such as critical thinking, digital literacy, and communication, and enhancing pedagogy by connecting language learning to real-world contexts. Furthermore, DSt enables students to learn at their own pace while empowering educators to inspire improved language acquisition. The study recommends that educational institutions conduct workshops and training to equip teachers with the technical and instructional skills needed to integrate digital storytelling, and that curriculum designers embed DSt projects into language education curricula to align with educational standards and learning objectives.